Somatic diversification of chicken immunoglobulin light chains by point mutations. - Parvari, R (1990)
The light-chain locus of chicken has 1 functional V lambda 1 gene, 1 J gene, and 25 pseudo-V lambda-genes (where V = variable and J = joining). A major problem is which somatic mechanisms expand this extremely limited germ-line information to generate many different antibodies. Weill's group [Reynaud, C. A., Anquez, V., Grimal, H. & Weill, J. C. (1987) Cell 48, 379-388] has shown that the pseudo-V lambda-genes diversify the rearranged V lambda 1 by gene conversion. Here we demonstrate that chicken light chains are further diversified by somatic point mutations and by V lambda 1-J flexible joining. Somatic point mutations were identified in the J and 3' noncoding DNA of rearranged light-chain genes of chicken. These regions were analyzed because point mutations in V lambda 1 are obscured by gene conversion; the J and 3' noncoding DNA are presented in one copy per haploid genome and are not subject to gene conversion. In rodents point mutations occur as frequently in the V-J coding regions as in the adjacent flanking DNA. Therefore, we conclude that somatic point mutations diversify the V lambda 1 of chicken. The frequency (0-1%) and distribution of the mutations (decreasing in number with increased distance from the V lambda 1 segment) in chicken were as observed in rodents. Sequence variability at the V lambda 1-J junctions could be attributed to imprecise joining of the V lambda 1 and J genes. The modification by gene conversion of rearranged V lambda 1 genes in the bursa was similar in chicken aged 3 months (9.5%) or 3 weeks (9.1%)--i.e., gene conversion that generates the preimmune repertoire in the bursa seems to level off around 3 weeks of age. This preimmune repertoire can be further diversified by somatic point mutations that presumably lead to the formation of antibodies with increased affinity. A segment with structural features of a matrix association region [(A + T)-rich and four topoisomerase II binding sites] was identified in the middle of the J-C lambda intron (where C = constant).